2004
DOI: 10.1158/1078-0432.ccr-04-1023
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitor Trichostatin A Represses Estrogen Receptor α-Dependent Transcription and Promotes Proteasomal Degradation of Cyclin D1 in Human Breast Carcinoma Cell Lines

Abstract: Conclusions: Tamoxifen has been shown to inhibit ER␣-mediated cyclin D1 transcription, and acquired resistance to tamoxifen is associated with a shift to ER␣-independent cyclin D1 up-regulation. Taken together, our data show that TSA effectively induces cyclin D1 down-regulation through both ER␣-dependent and ER␣-independent mechanisms, providing an important new strategy for combating resistance to antiestrogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
78
3
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 41 publications
14
78
3
1
Order By: Relevance
“…Collectively, these findings of down-regulation of growth-regulatory proteins suggest that sulforaphane may act as a HDAC inhibitor despite the lack of evidence for accumulation of global histone acetylation. The ability of sulforaphane to act as a HDAC inhibitor and down-regulate these proteins is consistent with previously published data indicating that the HDAC inhibitor trichostatin A down-regulates ER protein and the HDAC inhibitor LAQ824 down-regulates HER-2 protein through attenuation of mRNA levels and increased proteasomal degradation in human breast cancer cell lines (46,47).…”
Section: Discussionsupporting
confidence: 90%
“…Collectively, these findings of down-regulation of growth-regulatory proteins suggest that sulforaphane may act as a HDAC inhibitor despite the lack of evidence for accumulation of global histone acetylation. The ability of sulforaphane to act as a HDAC inhibitor and down-regulate these proteins is consistent with previously published data indicating that the HDAC inhibitor trichostatin A down-regulates ER protein and the HDAC inhibitor LAQ824 down-regulates HER-2 protein through attenuation of mRNA levels and increased proteasomal degradation in human breast cancer cell lines (46,47).…”
Section: Discussionsupporting
confidence: 90%
“…We previously reported that TSA provokes clearance of ERa from the breast carcinoma cell line MCF-7 , extending a previous report that butyric acid may also induce removal of ERa from cells (Stevens et al, 1984). More recently, Alao et al (2004) also demonstrate that TSA represses ERa mRNA synthesis. A second type of deacetylase activity, the sirtuins, also exists.…”
Section: Introductionsupporting
confidence: 82%
“…Our results showed that treatment of HepG2 cells with TSA facilitated IRF-1 degradation by the ubiquitin/proteasome pathway. Similar to our results, inhibition of HDAC activity by TSA also alters the function of several other important transcription factors, such as estrogen receptor a and steroidogenic factor 1, through targeting them for proteasomal degradation (45,46). CHIP was identified as an E3 ligase for IRF-1 as well as a number of HSP70-associated proteins, such as ErbB2 and PTEN (47,48); however, it was reported that CHIP acted as the chaperone for IRF-1 in unstressed cells.…”
Section: Discussionsupporting
confidence: 85%